2014
DOI: 10.3906/biy-1311-62
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome analysis of native Turkish cattle breeds by microsatellite markers

Abstract: The aim of this study was to determine phylogenetic relationships of 6 native cattle breeds of Turkey using 7 Y chromosomespecific microsatellite DNA markers. DNA samples were isolated from Anatolian Black, Anatolian Grey, South Anatolian Red, Native Southern Anatolian Yellow, East Anatolian Red, and Zavot cattle using a standard phenol/chloroform method. PCR products were separated by capillary electrophoresis and marker genotypes were determined. A total of 41 different alleles were observed. The mean allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…This points to the overall low diversity of the Y-chromosome markers, which may be due to either a low mutation rate or selection affecting the allelic diversity. It has been also shown that particular microsatellite alleles were either indicus-specific allele (INRA189 (88 bp) (Edwards et al, 2000), INRA124 (130 bp) (Edwards et al, 2000;Hanotte et al, 2000), and BM861 (156 bp) (Edwards et al, 2000;Özşensoy et al, 2014)) or were found only in a few individuals from indigenous breeds of different geographical origin (INRA189 (90 bp), INRA189 (82 bp) (Kantanen et al, 2009); INRA124 (134 bp) (Özşensoy et al, 2014)). Regarding studies of Y-chromosome microsatellites, up until now the highest diversity was observed in the INRA189 marker in a wide range of cattle breeds (Ginja et al, 2009;Kantanen et al, 2009;Cortes et al, 2011;Edwards et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This points to the overall low diversity of the Y-chromosome markers, which may be due to either a low mutation rate or selection affecting the allelic diversity. It has been also shown that particular microsatellite alleles were either indicus-specific allele (INRA189 (88 bp) (Edwards et al, 2000), INRA124 (130 bp) (Edwards et al, 2000;Hanotte et al, 2000), and BM861 (156 bp) (Edwards et al, 2000;Özşensoy et al, 2014)) or were found only in a few individuals from indigenous breeds of different geographical origin (INRA189 (90 bp), INRA189 (82 bp) (Kantanen et al, 2009); INRA124 (134 bp) (Özşensoy et al, 2014)). Regarding studies of Y-chromosome microsatellites, up until now the highest diversity was observed in the INRA189 marker in a wide range of cattle breeds (Ginja et al, 2009;Kantanen et al, 2009;Cortes et al, 2011;Edwards et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that microsatellites had been most frequently used in genetic characterization studies conducted in Asian and African countries [12]. In Turkey, genetic diversity studies with microsatellites had been conducted in goat [13], cattle [14, 15], and horse [16] populations.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of nucleotide and haplotype diversity, they showed higher values than other known world cattle breeds [2,4,5,6,7,8,10] when they were compared with all groups. Similarly, the Y chromosome specific markers in Turkish cattle breeds also showed high genetic diversity [26]. Genetic characterization which studied autosomal microsatellites and mtDNA reported that Turkish native cattle breeds had rich genetic diversity [10,27].…”
Section: Structure Of the Populationsmentioning
confidence: 99%
“…MtDNA D-loop region at position 15738 to 963 was amplified by forward primer (prot-RNA: CTGCAGTCTCACCATCAACC) [1] and revers primer (12SrNA-2: AGGATATAAAGCACCGCCAAG) [26]. Each multiplex for PCR was performed in 60μl reaction volume including 1x Mg ++ free PCR buffer (Fermentas), 0.125 mM dNTPs (Fermentas), 1.5 mM MgCl ++ , 0.375 U of Tag polymerase (Fermentas), 2 -17 pMol each primer and ~100 ng of genomic DNA.…”
Section: Amplification and Sequencingmentioning
confidence: 99%